Effects of the Addition of Ortho- and Para-NH2 Substituted Tetraphenylporphyrins on the Structure of Nylon 66 - Luis A. Díaz-Alejo; E. Carmina Menchaca-Campos; J. Uruchurtu Chavarín; R. Sosa-Fonseca; Miguel A. García-Sánchez (International Journal of Polymer Science)
The synthetic tetrapyrrole macrocycles, such as porphyrins (H2P) and phthalocyanines (H2Pc), exhibit interesting physicochemical properties suitable to be used in modern technology. For many applications, those species should be trapped or fixed inside graphite, hydrotalcites, silica, TiO2, or polymers. Methodologies for the optimization of the properties of porphyrins, trapped or fixed inside polymers, have been barely developed. Our research works in the development of methodologies for the optimization of incorporation and display of properties of tetrapyrrole macrocycles inside inorganic, polymeric, or hybrid networks. This paper shows some results about the effect of the spatial disposition of the amine (–NH2) groups attached on the periphery of substituted tetraphenylporphyrins, on the Nylon 66 structure and on the display of the physicochemical properties of the trapped macrocycles. Nylon 66 was synthesized from adipoyl chloride and hexamethylenediamine in presence of tetraphenylporphyrins substituted with –NH2 groups localized at the ortho- or para-positions of the phenyls. Cobalt complexes formation was used to quantify the amount of porphyrins in the polymer fibers. Characterization results show that the spatial position of amine groups of the porphyrins has important structural and textural effect on the Nylon 66 fibers and on the fluorescence of the porphyrins integrated into the fibers.